Analysis of the STEM-Based Blended Project Based Learning Model to Improve Students' Science Literacy - Kurniasari, Ris; Ridho, Saiful; Indriyanti, Dyah Rini (Journal of Innovative Science Education, 2023)
The purpose of the study was to analyze the application of the STEM-based Blended Project Based Learning model in improving scientific literacy skills and student learning activities. This research is a Research and Development (R&D), the product developed is a STEM-based blended project based learning model contained in the Syllabus, Learning Implementation Plan, evaluation tools, and Student Worksheets. The research design used One group pretest-posttest design. Data were collected using test and non-test methods, to measure aspects of scientific literacy skills and student activities in learning. The research subject is grade of VII SMP 1 Mejobo Kudus.The data analysis technique was carried out by descriptive analysis and inferential statistics (N-gain test). The results of the validation of the STEM-Based Blended Project Based Learning model for environmental pollution materials developed obtained valid criteria for use in learning. Characteristics STEM-based blended project-based learning model developed based on six main pillars, namely curriculum centered, contextual, real problem-based, constructive investigation, realistic projects and student autonomy. Application STEM-based blended project-based learning model meet the eligibility criteria. This is indicated by the average result of the classical science literacy test is 70.11 and the proportion of classical learning completeness meets 75 out of 105 complete KKM 70, and the average N-gain achievement is 0.40 in the medium category. The results of the analysis of the observation of student learning activities obtained the highest score or percentage, namely 71.90% in the good category. Student response to implementation STEM-based blended project-based learning model received a positive response from students with a mean score of 72.30 with the criteria of "agree".